On Ideally Slowly Oscillating Continuity in Abstract Space: Bipan Hazarika, Ayhan Esi - Team, Support (Thai Journal of Mathematics, 2021)
In this paper, we introduce the notion of ideally slowly oscillating sequences, which is lying between ideal convergent and ideal quasi-Cauchy sequences, and study on ideally slowly oscillating continuous functions in topological vector space valued cone metric space. Also we introduce the notion of strongly continuous on topological vector space valued cone metric space and investigated some new results related to this notion.